Indonesian Government’s Effort to Defend Children from Abuse - Bilqisti, Sabrina; Zahira, Alya; Muttaqien, Hisyam Ihza; Ernawati, Ernawati (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
This journal is done through observations of pressing issues surrounding human rights for children and their protection. It is aimed to look deeper into the condition of children in Indonesia which is said to be protected by the Indonesian government under human rights laws. The violations around children consist ofÂ children carrying the burden to provide for their families under harsh circumstances. Everyday, children on the streets ask for money, teenagers working in the cities as maids, when they all are supposed to be in school. Child labor revolves around pedophilia, child labor, and child physical and mental abuse. These are mostly done by adults for their personal needs and children are not taken as seriously as they are seen as minors, thus disregarding their feelings. Indonesia government should further investigate on this matter to prevent more child abuse happening in Indonesia. Awareness of child abuse are further observed through surveys from Indonesian general public to determine the perspective towards their consciousness towards this issue. Children should be the main priority as they are the future, thus protection should be more advanced.